Produtos biológicos e alternativos no controle de doenças pós-colheita em melão cantaloupe - Moura, Renata Damasceno (2007)
The aim this study was to evaluate the effect of the application of biological, alternative and chemical products on the control of postharvest diseases and conservation of Cantaloupe melon. In the control experiment in vitro (Test of Antagonist) was verified the ocorrence of antagonistic between isolates of Trichoderma (SN11, T15, T25, TR2) with relation the all pathogenic isolates to melon (Fusarium sp, Aspergillus niger, Aspergillus flavus, Rhizopus stlonifer and Lasiodiplodia theobromae). For the treatments, the most effective in the inhibition of the fungi mycelial growth were the nature fungicide 20 mL-1 and Lippia sidoides, that were effectives in 100% to all evaluated fungi; the Cymbopogum citratus was only less effective on the A. flavus fungi (75,3%) and the Imazalil fungicide has lower efficiency on the R stolonifer fungi (1,54%). The treatment with nature fungicide 2mL-1 has higher efficiency in relation to Fusarium sp and L. theobromae, with inhibitions of 88,9 and 86,2% respectively, and lower efficciency on the R. stolonifer (3,3%). In assay in vivo it was used split spot in a completely randomized design, with three replicates and three fruits for treatment. In the spots were alloted the periods of storage (0, 7, 14, 21 and 28 days) and the subplots, the treatments (Trichoderma + hipoclorito), (Trichoderma without hipoclorito), (nature fungicide 20 mL-1), (nature fungicide 2 mL-1), (essential oil of Cymbopogum citratus 2 mL-1), (essential oil of Lippia sidoides 2 mL-1), (Chemical Imazalil 1 mL-1) and (Control - application of destiled water). After the treatments, the fruits were conservated in boxes of paper, it using modify atmosphere with poliméricos films xtend and stored in a temperature of 6°C and UR 90±5%. The fruits were evaluated with relation to incidence of diseases, external and internal appearences, color, loss of matter fresh, pulp firmness, soluble solids, total soluble sugar, pH and titritable total acidity at 7, 14, 21 and 28 days after the period of storage of three days at 22º C ± 2º C and UR of 50% ± 5%. It was observed significant interation between treatments and storage time for occurence of disease, extern and intern appearence, color, titritable total acidity, pH and soluble solids. For the variable loss of fresch mass, it was verified that the treated fruits with nature fungicide 20 and 2 mL.L-1, Lippia sidoides and Cymbopogum citratus presented lower values, did not differing between them nor of the treatment with destiled water. The pulp firmness of treated fruits with Trichoderma (T1) presented value of 26,19 N and differed only of Trichoderma without hipoclorito (T2) and Cymbopogum citratus (T5), that showed fruits less firm (20,51 and 22,72 N, respectively). There was not statistical difference between treatments for the variables: soluble solids and total soluble sugar. The nature fungicide 20 mL1 Trichoderma with hipoclorito, Lippia sidoides and Imazalil were the treatments most effectives in the control of postharvest diseases of Cantaloupe hybrids melon ( Hy Mark )